The Physical activity as an element of non-pharmacological asthma therapy - Matuszek, Anna; Siedy-Florek, Ewa; Stawowy, Zofia; Strzeszyna, Maja; Szlachetka, Katarzyna; Chołda, Julia; Janik, Wiktoria; Jamontt, Kinga; Manasar, Aleksander; Matlakiewicz, Magdalena (Quality in Sport, 2025)
Asthma is a chronic inflammatory airway disease that is marked by variable airflow limitation and hyperresponsiveness of the airways. Although pharmacologic management remains the mainstay of asthma therapy, physical exercise and other non-pharmacologic treatments are increasingly found to have an adjunctive function in the disease control. The present review collates available information on the role of physical training as an add-on therapy in the treatment of asthma. It focuses on how proper regular exercise can enhance pulmonary function, reduce symptom burden, and improve quality of life. Particular attention is given to the swimming environment and its multidirectional interaction with asthma, such that exposure to chlorinated by-products can enhance airway inflammation even as the activity has beneficial physiological effects. The article also addresses the physiological mechanisms of exercise-induced asthma (EIA), recommended exercise modalities and intensities, and assessment of physical activity in asthmatic patients. The overall results point to the necessity of individualized, multidisciplinary management encompassing both medical and lifestyle intervention in the treatment of asthma.